The miRNA transcriptome of cerebrospinal fluid in preterm infants reveals the signaling pathways that promote reactive gliosis following cerebral hemorrhage - Gialeli, Andriana; Spaull, Robert; Plösch, Torsten; Uney, James; Llana, Oscar Cordero; Heep, Axel (Frontiers in Molecular Neuroscience, 2023)
Introduction Germinal Matrix-Intraventricular Haemorrhage (GM-IVH) is one of the most common neurological complications in preterm infants, which can lead to accumulation of cerebrospinal fluid (CSF) and is a major cause of severe neurodevelopmental impairment in preterm infants. However, the pathophysiological mechanisms triggered by GM-IVH are poorly understood. Analyzing the CSF that accumulates following IVH may allow the molecular signaling and intracellular communication that contributes to pathogenesis to be elucidated. Growing evidence suggests that miRs, due to their key role in gene expression, have a significant utility as new therapeutics and biomarkers. Methods The levels of 2,083 microRNAs (miRs) in 15 CSF samples from 10 infants with IVH were measured using miRNA whole transcriptome sequencing. Gene ontology (GO) and miR family analysis were used to uncover dysregulated signalling which were then validated in vitro in human foetal neural progenitor cells treated with IVH-CSF. Results Five hundred eighty-seven miRs were differentially expressed in the CSF extracted at least 2 months after injury, compared to CSF extracted within the first month of injury. GO uncovered key pathways targeted by differentially expressed miRs including the MAPK cascade and the JAK/STAT pathway. Astrogliosis is known to occur in preterm infants, and we hypothesized that this could be due to abnormal CSF-miR signaling resulting in dysregulation of the JAK/STAT pathway – a key controller of astrocyte differentiation. We then confirmed that treatment with IVH-CSF promotes astrocyte differentiation from human fetal NPCs and that this effect could be prevented by JAK/STAT inhibition. Taken together, our results provide novel insights into the CSF/NPCs crosstalk following perinatal brain injury and reveal novel targets to improve neurodevelopmental outcomes in preterm infants.